Pre-failure deformation behaviour of geomaterials - Jardine, R. J. (Thomas Telford, 1998)
Based on the symposium held by the Institution of Civil Engineers in 1997, this text details international papers from leading names within the fields of soil and rock mechanics engineering geology and environmental geotechnics.
At head of title: Institution of Civil Engineers.
Keywords: Deformations (Mechanics) -- Congresses.; Soil mechanics -- Congresses.; Rock mechanics -- Congresses.; elektronické knihy; electronic books